2021
DOI: 10.1002/jcla.24026
|View full text |Cite
|
Sign up to set email alerts
|

The study of routine laboratory factors in children with mycoplasma pneumoniae pneumonia: serum uric acid may have anti‐inflammatory effect

Abstract: Background High uric acid levels are a risk factor for cardiovascular disorders, and metabolic diseases; however, the role of serum uric acid (sUA) during the mycoplasma pneumoniae pneumonia (MPP) of children is poorly known. This study aimed to clarify the effects of sUA during the MPP of children. Methods This was a prospective cohort study of children with MPP from multi‐center inpatient departments from September 2019 to August 2020. Routine laboratory characteristics analyzed including ALT, AST, BUN, CREA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…According to the results, children with bronchitis and pneumonia have a higher level of WBC and higher expression of inflammatory factors such as CRP, IL-6, and TNF-α. After the proper treatment, the four indicators have significantly decreased [16,17]. Moreover, the treatment with ambroxol hydrochloride combined with amoxicillin potassium clavulanate combination resulted in lower WBC and inflammatory factors as compared with amoxicillin potassium clavulanate combination, suggesting a prominent efficacy of ambroxol hydrochloride combined with amoxicillin potassium clavulanate combination in the treatment of bronchitis pneumonia in children.…”
Section: Discussionmentioning
confidence: 96%
“…According to the results, children with bronchitis and pneumonia have a higher level of WBC and higher expression of inflammatory factors such as CRP, IL-6, and TNF-α. After the proper treatment, the four indicators have significantly decreased [16,17]. Moreover, the treatment with ambroxol hydrochloride combined with amoxicillin potassium clavulanate combination resulted in lower WBC and inflammatory factors as compared with amoxicillin potassium clavulanate combination, suggesting a prominent efficacy of ambroxol hydrochloride combined with amoxicillin potassium clavulanate combination in the treatment of bronchitis pneumonia in children.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism of the reduced serum uric acid levels in RMPP patients is unknown.The study found that the concentration of uric acid in respiratory epithelial tissue uid was high, and the uric acid of respiratory epithelial lining uid played the antioxidant effect of together with other endogenous antioxidants and ascorbic acid (22).Uric acid was found to act as an endogenous modulator of innate immunity, so it is tempting to speculate that low levels of serum uric acid may exacerbate the cytokine storm during COVID-19 (23,24).Recent evidence suggests that acute and severe hypouricaemia induced in healthy individuals causes endothelial cell dysfunction (25). Recently, researchers have focused on serum uric acid levels in COVID-19, believing that hyperuricemia in COVID-19 patients may lead to acute kidney injury and adverse outcome(26).A most recent clinical study showed that serum uric acid exhibits protective effects in the pediatric MPP process, with an anti-in ammatory effect on (27). All the above suggest that reduced serum uric acid level is a risk factor for disease, but the speci c mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 Another study demonstrated serum UA exerted anti-inflammation and protective effects on the mycoplasma pneumoniae pneumonia in children. 49 The ability of UA to reduce oxidative stress and inflammation is well established in pneumonia. In an earlier study, we found that serum UA was a protective factor for in-hospital pneumonia after ICH in a large population.…”
Section: Discussionmentioning
confidence: 99%